2011
DOI: 10.1080/09712119.2011.637362
|View full text |Cite
|
Sign up to set email alerts
|

Trends in goat research, a review

Abstract: The present review covers the main topics related to goats for the last two years. The main topics were pathology, reproduction, milk and cheese production and quality, production systems, nutrition, hair production, drugs knowledge and meat production. Especially energy use by goats in different conditions and the role of somatic cell count in intramammary infections and milk and cheese quality are discussed. Goat research needs progress rapidly to reach the level of knowledge of other species like cattle or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 52 publications
0
33
0
Order By: Relevance
“…Broderick and Reynal (2009) reported that increased dietary protein levels increased dry matter (DM) digestibility in lactating cows fed at high levels of intake. Increasing the CP content of dairy cow diets may result not only in greater milk production, but also in increased concentrations of ruminal ammonia and blood urea N (BUN; Orskov 1994;Hristov et al 2004;Argüello 2011). However, diets containing an excess of protein are considered undesirable because the excess N is excreted, resulting in a net loss of N (Broderick 2003;Cherdthong et al 2011aCherdthong et al , 2011b.…”
Section: Introductionmentioning
confidence: 99%
“…Broderick and Reynal (2009) reported that increased dietary protein levels increased dry matter (DM) digestibility in lactating cows fed at high levels of intake. Increasing the CP content of dairy cow diets may result not only in greater milk production, but also in increased concentrations of ruminal ammonia and blood urea N (BUN; Orskov 1994;Hristov et al 2004;Argüello 2011). However, diets containing an excess of protein are considered undesirable because the excess N is excreted, resulting in a net loss of N (Broderick 2003;Cherdthong et al 2011aCherdthong et al , 2011b.…”
Section: Introductionmentioning
confidence: 99%
“…The use of locally available feed resources has great potential for improving goat production in developing countries (Argu¨ello 2011). Iran is considered to be the largest producer of pistachio worldwide, with an annual production of approximately 500,000 tons of fresh pistachio by-products (PBP; Shakeri et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the same sense, Wilde et al (1987) observed, after 37 weeks, greater amounts of RNA, DNA and several key enzymes in thrice-daily milking glands compared with twice-daily milking glands. In contrast, Stelwagen et al (1994) described that after 36 h of milk accumulation, mammary tight junctions (TJ) had become disrupted, reducing synthetic activity and inducing apoptosis (Chedly et al 2010;Argu¨ello 2011). In dairy cows, several studies support the concept that serotonin (5-HT) is a feedback inhibitor of lactation (Hernandez et al 2008).…”
Section: Introductionmentioning
confidence: 99%